Atensi as a Social Rehabilitation Effort for Persons with Visual Disabilities at Sentra Terpadu Pangudi Luhur Bekasi - Siska, Meilia Rike Fitrinia; Rahayu, Ety (International Journal of Science and Society, 2025)
Social rehabilitation is an effort to fulfill the basic needs and restore the functions of persons with disabilities. The Ministry of Social Affairs has introduced the Asistensi Rehabilitasi Sosial (ATENSI) program, which aims to enhance the abilities of persons with disabilities in self-care, self-protection, self-actualization, and/or social participation, as well as to improve their income as beneficiaries of the program. This initiative not only focuses on fulfilling physical and economic needs but also emphasizes psychosocial support, empowerment, and strengthening an inclusive social environment so that persons with disabilities can live independently and actively participate in society. The Sentra Terpadu Pangudi Luhur (STPL) is an integrated center formed from the merger of three social rehabilitation institutions serving three clusters: older persons (BRSLU Budi Dharma Bekasi), persons with visual disabilities (BRSPDSN Tan Miyat Bekasi), and homeless and beggars (BRSEGP Pangudi Luhur Bekasi). This integration creates challenges in optimizing resources for implementing the ATENSI program. This study aims to describe the implementation of the ATENSI program for persons with visual disabilities managed by the Sentra Terpadu Pangudi Luhur Bekasi. The research used a qualitative descriptive approach to analyze the stages of the ATENSI program implementation. The findings reveal that the ATENSI implementation consists of eight stages: access facilitation; engagement intake and engagement; comprehensive and continuous assessment; intervention planning; implementation; supervision, monitoring, and evaluation; and post-service and termination. These stages are aligned with the Generalist Intervention Model proposed by Kirst-Ashman and Hull (2018).